Electrocatalyst ink

Through the contact of the preparation of the electro -catalyst ink, the dispersion body and the cheap metal binding agent are exposed to remove cheap metal pollutants, solving the problem of low electrochemical chemical performance of membrane electrode components, and realizing performance improvement.

CN114651351BActive Publication Date: 2025-01-28JOHNSON MATTHEY HYDROGEN TECH LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202080077191.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-05-19
Filing Date
2020-12-11
Publication Date
2025-01-28
Estimated Expiration
2040-12-11

AI Technical Summary

Technical Problem

The electrochemical properties of existing membrane electrode assemblies are affected by base metal contaminants, resulting in lower performance than expected.

Method used

When preparing the ink of electrical catalysts, add a cheap metal binding agent to contact the scattered body and the cheap metal binding agent to remove the cheap metal pollutants entering the electrocatalyst layer.

Benefits of technology

The membrane electrode component of the electrocatalyst layer prepared through this method shows improved electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114651351B_ABST
    Figure CN114651351B_ABST
Patent Text Reader

Abstract

The present invention provides a method of preparing an electrocatalyst ink, the method comprising the step of contacting a dispersion with a base metal binder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a method for preparing electrocatalyst ink. The electrocatalyst ink is used to prepare an electrocatalyst layer in a high-performance membrane electrode assembly. Background Art

[0002] A fuel cell is an electrochemical cell comprising two electrodes separated by an electrolyte. A fuel (e.g., hydrogen, an alcohol (such as methanol or ethanol) or formic acid) is supplied to the anode, and an oxidant (e.g., oxygen or air) is supplied to the cathode. An electrochemical reaction occurs at the electrodes, and the chemical energy of the fuel and oxidant is converted into electrical energy and heat. An electrocatalyst is used to promote the electrochemical oxidation of the fuel at the anode and the electrochemical reduction of oxygen at the cathode.

[0003] Fuel cells are generally classified according to the nature of the electrolyte used. The electrolyte is generally a solid polymer membrane, wherein the membrane is electrically insulating but ionically conductive. In a proton exchange membrane fuel cell (PEMFC), the ion-conducting membrane is proton-conducting, and protons generated at the anode are transported across the ion-conducting membrane to the cathode, where they combine with oxygen to form water.

[0004] The main component of a PEMFC is a membrane electrode assembly, which is essentially composed of five layers. The middle layer is a polymer ion-conducting membrane. On either side of the ion-conducting membrane there is an electrocatalyst layer containing an electrocatalyst designed for a specific electrolysis reaction. Finally, adjacent to each electrocatalyst layer there is a gas diffusion layer. The gas diffusion layer must allow reactants to reach the electrocatalyst layer and must conduct the current generated by the electrochemical reaction. Therefore, the gas diffusion layer must be porous and conductive.

[0005] The electrocatalyst layer also generally comprises a proton conducting material, such as a proton conducting polymer, to facilitate the transfer of protons from the anode electrocatalyst to the ion conducting membrane and / or from the ion conducting membrane to the cathode electrocatalyst.

[0006] Conventionally, membrane electrode assemblies can be constructed by a variety of methods. Typically, these methods involve applying one or two of the electrocatalyst layers to an ion-conducting membrane to form a catalyst-coated ion-conducting membrane. Subsequently, a gas diffusion layer is applied to the electrocatalyst layer. Alternatively, the electrocatalyst layer is applied to the gas diffusion layer to form a gas diffusion electrode, which is then combined with the ion-conducting membrane. The membrane electrode assembly can be prepared by a combination of these methods, for example, applying one electrocatalyst layer to an ion-conducting membrane to form a catalyst-coated ion-conducting membrane, and applying another electrocatalyst layer as a gas diffusion electrode. The electrocatalyst layer is applied using an electrocatalyst ink that typically contains an electrocatalyst material, an ion-conducting polymer, a solvent and / or a diluent, and any reagents that are desired to be included in the electrocatalyst layer.

[0007] The electrocatalyst layer typically comprises an electrocatalyst material comprising a metal or metal alloy suitable for fuel oxidation or oxygen reduction reaction, depending on whether the layer is to be used for the anode or cathode. Electrocatalysts for fuel oxidation and oxygen reduction are typically based on platinum or platinum alloyed with one or more other metals. Platinum or platinum alloy electrocatalysts can be in the form of unsupported nanosized particles (e.g., metallic black), or can be deposited as discrete very high surface area nanoparticles onto a support material (supported electrocatalyst). The electrocatalyst can also be in the form of a coating or extended film deposited onto a support material.

[0008] Various electrocatalyst concepts have been investigated, such as platinum binary alloys, platinum, monolayer electrocatalysts, platinum skin electrocatalysts, and nanostructured thin film (NSTF) electrocatalysts. Another approach to reported highly active electrocatalysts is the dealloyed Pt-M concept materials obtained by synthesizing base metal (M)-rich particles that are subjected to a process of selectively leaching less noble metals from the particle surface. The resulting platinum-rich shell of the dealloyed electrocatalyst particles exhibits compressive strain, which leads to highly active oxygen reduction reaction (ORR) catalysts through electronic effects. Summary of the invention

[0009] The inventors have recognized that the performance of a membrane electrode assembly can be improved by removing base metal contaminants that enter the electrocatalyst layer during the preparation of the membrane electrode assembly. For example, base metal species can be leached from alloys of platinum group metals and base metals during the preparation of the electrocatalyst ink because the agglomerates are broken up in the presence of acidic ion-conducting polymers. This can result in lower than expected electrochemical performance of the membrane electrode assembly. Contaminating base metal species may also be present in an electrocatalyst layer that does not contain an alloy electrocatalyst. Contaminants may come from, for example, the manufacturing process for preparing the electrocatalyst, or the manufacture of ion-conducting polymers. Therefore, there is a need to improve the performance of membrane electrode assemblies contaminated with base metal species.

[0010] Therefore, in a first aspect, the present invention provides a method for preparing an electrocatalyst ink, the method comprising the steps of:

[0011] i) preparing a dispersion comprising an electrocatalyst material, an ion-conducting material and a diluent; then

[0012] ii) contacting the dispersion with a base metal binder.

[0013] An electrocatalyst ink is a dispersion comprising an electrocatalyst material, an ionically conductive material and a diluent, which dispersion when dried forms an electrocatalyst layer, preferably an electrocatalyst layer in a fuel cell membrane electrode assembly.

[0014] The present inventors surprisingly found that a membrane electrode assembly containing an electrocatalyst layer prepared using an ink produced by this method can exhibit improved electrochemical performance compared to a membrane electrode assembly containing an electrocatalyst layer prepared by a method not comprising step ii).

[0015] In a second aspect, the present invention provides a dispersion comprising an electrocatalyst material, an ionically conductive material, a base metal binder and a diluent. Such a dispersion is prepared as part of the method of the first aspect of the present invention.

[0016] In a third aspect, the present invention provides a method of applying an electrocatalyst layer to a substrate, the method comprising the steps of:

[0017] i) preparing an electrocatalyst ink by the method of the first aspect of the present invention; then

[0018] ii) applying an electrocatalyst ink to said substrate and drying the ink to form an electrocatalyst layer. In a fourth aspect, the present invention provides an electrocatalyst layer obtainable by this method.

[0019] In a fifth aspect, the present invention provides a method for preparing a gas diffusion electrode, the method comprising applying an electrocatalyst layer to a substrate according to the method of the third aspect of the present invention, wherein the substrate is a gas diffusion layer. In a sixth aspect, the present invention provides a gas diffusion electrode obtainable by this method.

[0020] In a seventh aspect, the present invention provides a method for preparing a catalytic transfer substrate, the method comprising applying an electrocatalyst layer to a substrate according to the method of the third aspect of the present invention, wherein the substrate is a face of a transfer substrate. In an eighth aspect, the present invention provides a catalytic transfer substrate, which can be obtained by this method.

[0021] In a ninth aspect, the present invention provides a method for preparing a catalyst-coated ion-conducting membrane, the method comprising applying an electrocatalyst layer to a substrate according to the method of the third aspect of the present invention, wherein the substrate is the face of the ion-conducting membrane. In a tenth aspect, the present invention provides a method for preparing a catalyst-coated ion-conducting membrane, the method comprising applying the electrocatalyst layer to the ion-conducting membrane by transfer from a catalytic transfer substrate prepared according to the method of the seventh aspect of the present invention. In an eleventh aspect, the present invention provides a catalyst-coated ion-conducting membrane, which can be obtained by these methods.

[0022] In a twelfth aspect, the present invention provides a method for preparing a membrane electrode assembly, the method comprising the following steps;

[0023] i) preparing a gas diffusion electrode according to the method of the fifth aspect of the present invention;

[0024] ii) applying the gas diffusion electrode prepared in step i) to the face of the ion-conducting membrane. In a thirteenth aspect, the present invention provides a membrane electrode assembly obtainable by this method.

[0025] In a fourteenth aspect, the present invention provides a method for preparing a membrane electrode assembly, the method comprising the following steps;

[0026] i) preparing a catalyst-coated ion-conducting membrane according to the method of the ninth aspect or the tenth aspect of the present invention;

[0027] ii) applying a gas diffusion layer to the electrocatalyst layer. In a fifteenth aspect, the present invention provides a membrane electrode assembly obtainable by this method.

[0028] In a sixteenth aspect, the present invention provides a fuel cell comprising a membrane electrode assembly according to the present invention. Preferably, the fuel cell is a proton exchange membrane fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 : is a graph showing the relationship between voltage and current density of a membrane electrode assembly including a cathode electrocatalyst layer prepared using the method of the present invention and a comparative membrane electrode assembly at 100% relative humidity.

[0030] Figure 2 The graph is a graph showing the relationship between voltage and current density of a membrane electrode assembly including a cathode electrocatalyst layer prepared using the method of the present invention and a comparative membrane electrode assembly at 50% relative humidity.

[0031] Figure 3 The graph is a graph showing the relationship between voltage and current density of a membrane electrode assembly including a cathode electrocatalyst layer prepared using the method of the present invention and a comparative membrane electrode assembly at a relative humidity of 26%. DETAILED DESCRIPTION

[0032] The preferred and / or optional features of the present invention will now be described. Unless the context otherwise requires, any aspect of the present invention may be combined with any other aspect of the present invention. Unless the context otherwise requires, any of the preferred or optional features of any aspect may be combined with any aspect of the present invention individually or in combination.

[0033] When an entity is referred to as "the present invention", a non-limiting example is "the electrocatalyst layer of the present invention", which means that the entity is prepared by the corresponding method of the present invention, or can be obtained by the corresponding method of the present invention. Thus, for example, the electrocatalyst layer of the present invention is an electrocatalyst layer prepared by the method of the third aspect of the present invention, or is an electrocatalyst layer obtainable by the method of the third aspect of the present invention (i.e., the fourth aspect of the present invention).

[0034] The electrocatalyst material comprises an electrocatalyst, which is preferably a platinum group metal or an alloy of a platinum group metal and a base metal, preferably an alloy of a platinum group metal and a base metal. Platinum group metals include platinum, palladium, rhodium, ruthenium, iridium and osmium. Preferred platinum group metals in both platinum group metals and alloy electrocatalysts are platinum, palladium and rhodium, and most preferably platinum. The base metal is tin or a transition metal that is not a noble metal. The noble metal is a platinum group metal (platinum, palladium, rhodium, ruthenium, iridium or osmium) or gold. Suitable base metals in alloy electrocatalysts are copper, cobalt, nickel, zinc, iron, titanium, molybdenum, vanadium, manganese, niobium, tantalum, chromium and tin. Preferred base metals in alloy electrocatalysts include nickel, copper, cobalt and chromium. More preferred base metals are nickel, cobalt and copper. The most preferred base metal is nickel. The ratio of platinum group metals to base metals in alloy electrocatalysts is generally in the range of 3:1 to 1:3 and includes these end values. The alloy electrocatalyst can be a dealloyed electrocatalyst. In other words, the atomic composition of the platinum group metal relative to the base metal at the surface of the electrocatalyst is lower than the atomic composition of the platinum group metal relative to the base metal in the electrocatalyst as a whole, where the whole is the total composition of the electrocatalyst. For example, the atomic composition of the platinum group metal relative to the base metal at the surface of the electrocatalyst may be in the range of 20% to 99%, 20% to 70%, or 30% to 55% of the atomic composition of the platinum group metal relative to the base metal in the electrocatalyst as a whole and includes these end values. The electrocatalyst may be an anode or cathode electrocatalyst, and is preferably a proton exchange membrane fuel cell electrocatalyst. Therefore, the electrocatalyst may be a hydrogen oxidation reaction (anode) or an oxygen reduction reaction (cathode) electrocatalyst.

[0035] The electrocatalyst may be supported or unsupported. Thus, the electrocatalyst may be supported on a support material. In other words, the electrocatalyst material may consist of (or only include) an electrocatalyst supported on a support material. The term "supported" will be readily understood by the skilled person. For example, it will be understood that the term "supported" includes an electrocatalyst dispersed on a support material and bound or fixed to the support material by physical or chemical bonds. For example, the electrocatalyst may be bound or fixed to the support material by ionic bonds or covalent bonds, or non-specific interactions (such as van der Waals forces).

[0036] The support material may be a carbon support material, such as a carbon powder, which may be, for example, commercially available carbon black (such as from Cabot Corp. XC72R) or Akzo Nobel( Black series) or graphitized versions of these carbon blacks or other commercially available carbon blacks, such as acetylene black (e.g., available from Chevron Phillips (Shawinigan ) or those of Denka). The support material may also be a support material specially designed for use in fuel cells, such as those described in WO2013 / 045894.

[0037] Alternatively, the support material may be a metal oxide or mixed oxide (particularly a conductive mixed oxide, such as niobium-doped titanium dioxide, phosphorus-doped tin oxide and mixed platinum group metal oxides or mixed metal oxides as disclosed in WO2012 / 080726), a carbide (e.g. tungsten carbide, molybdenum carbide or titanium carbide, suitably tungsten carbide or titanium carbide), a nitride (particularly a conductive nitride (e.g. titanium nitride or titanium aluminum nitride)).

[0038] When the electrocatalyst is supported on a support material, the electrocatalyst loading may be expressed as a weight percent of active metal (e.g., a weight percent of platinum group metal), which may be determined using inductively coupled plasma mass spectrometry (ICPMS). The loading may suitably be at least 10 weight percent platinum group metal, typically at least 20 weight percent platinum group metal, based on the total weight of the electrocatalyst and the support. The electrocatalyst loading may suitably be no more than 90 weight percent platinum group metal, typically no more than 60 weight percent platinum group metal, for example no more than 50 weight percent platinum group metal, based on the total weight of the electrocatalyst and the support material.

[0039] The solid content of the electrocatalyst ink after contacting with the base metal binder and (if necessary) removing the base metal binder is not particularly limited, and will depend on the printing method to be used to prepare the electrocatalyst layer by the ink. Solid content includes electrocatalyst material, ion conductive material and any other solid present. For example, by the total weight of the electrocatalyst ink, the solid content may not exceed 25 weight %, and is suitably at least 5 weight %. Specifically, the electrocatalyst ink for screen printing may suitably contain solids in the range of 20 weight % to 25 weight % and including these end values, the electrocatalyst ink for slot die printing may suitably contain solids in the range of 10 weight % to 15 weight % and including these end values, and the electrocatalyst ink for gravure printing may suitably contain solids not exceeding 10 weight %.

[0040] The ion-conducting material is suitably a proton-conducting ionomer. The skilled person will appreciate that an ionomer is a polymer composed of both electrically neutral repeating units and ionizable repeating units covalently bonded to the polymer backbone via side chains. The ion-conducting material may include ionomers such as perfluorosulfonic acid (e.g. (Chemours Company), (AsahiKasei)、 (Solvay Specialty Polymer), (Asahi Glass Co.), or ionomers based on partially fluorinated or non-fluorinated hydrocarbon sulfonated or phosphinated polymers, such as those available from FuMA-Tech GmbH (as P, E or K series products), those of JSR Corporation, Toyobo Corporation, etc. Suitably, the ionomer is a perfluorosulfonic acid preferably having an EW in the range of 600 to 1200, inclusive, where the EW or equivalent weight is the grams of dry polymer per mole of sulfonic acid groups when the material is in the acid form. Specific perfluorosulfonic acid ionomers include those available from Chemours company. Series (especially 1100EW and DE2020CS), purchased from Solvay series (especially 830EW).

[0041] The dispersion also includes a diluent. Suitable diluents include organic solvents and water, preferably a mixture of one or more organic solvents and water. However, water alone can be used as a diluent. The amount of the diluent is not particularly limited, and will depend on the printing method to be used to prepare the electrocatalyst layer by the ink. Therefore, it will be adjusted for the desired solid content (discussed above). Suitable organic solvents are alcohol-based solvents, preferably propanol or ethanol, such as propan-1-ol. In a mixture of an organic solvent and water, the weight percentage of the organic solvent is suitably no more than 85% by weight and is at least 10% by weight, based on the total weight of the diluent. When the mixture contains no more than 5% by weight of an organic solvent, for example no more than 1% by weight, and the remainder is water, the dispersion may also include a mineral acid as described in WO 2006 / 233187. A specific example of a diluent is a mixture of propan-1-ol and water, such as a mixture of propan-1-ol and water containing about 80% by weight of propan-1-ol. An alternative example of a diluent is a mixture of ethanol and water, for example containing 10% to 50% by weight, suitably about 25% by weight, of ethanol. An alternative example of a diluent is a mixture of ethanol, propan-1-ol and water, which may contain more propan-1-ol than ethanol, for example 5% to 15% by weight, suitably about 10% by weight, of ethanol and 50% to 70% by weight, suitably about 70% by weight of propan-1-ol, the remainder being water.

[0042] Agglomerate particle breakage is preferably performed by methods known in the art (such as high shear mixing, grinding, ball milling, by microfluidizer or a combination thereof) before contact with the base metal binder. For example, when the electrocatalyst material is supported on a carrier material, the agglomerates may include loosely held individual carrier particles or agglomerates held together by weak forces, and may be easily decomposed into individual carrier particles or agglomerates by such low energy agitation. Agglomerates of the electrocatalyst may also be formed when the electrocatalyst is not supported, and such agglomerates may also be easily decomposed.

[0043] The term "base metal binder" means an agent capable of associating with a base metal species (preferably a cation of a base metal) so that the base metal species can be separated from the dispersion. Thus, the base metal binder removes free base metal species (e.g., base metals that do not form part of the electrocatalyst) from the dispersion. The base metal is tin or a transition metal that is not a noble metal. The noble metal is a platinum group metal (platinum, palladium, rhodium, ruthenium, iridium or osmium) or gold. Suitable base metals are iron, copper, cobalt, nickel, zinc, iron, titanium, molybdenum, vanadium, manganese, niobium, tantalum, chromium and tin. The amount of free base metal species in the dispersion before contact with the base metal binder is not particularly limited and may be, for example, not more than 3000 ppm, suitably not more than 2500 ppm. After the step of contacting the dispersion with the base metal binder, the resulting electrocatalyst ink typically contains not more than 2000 ppm of base metal species, suitably not more than 1500 ppm. Thus, in this example, the base metal binder is capable of removing about 1000 ppm, suitably about 500 ppm, of base metal species. The base metal binder is capable of binding (i.e., capable of separating from the dispersion) base metal species, including, for example, iron, nickel, copper, cobalt and chromium species, preferably cations, such as Fe 2+ , Fe 3+ 、Ni 2+ , Cu 2+ 、Co 2+ Cr 2+ and Cr 3+ In particular, it is capable of binding iron, nickel and / or cobalt species, preferably cations such as Fe 2+ , Fe 3+ 、Ni 2+ and Co 2+ , preferably it is capable of binding nickel and / or cobalt species, preferably cations such as Ni 2+ and Co 2+ Although this is not a requirement of the present invention, base metal species may result from unintentional leaching of the alloy electrocatalyst or other causes. For example, free nickel and cobalt species may result from leaching of the electrocatalyst (which is an alloy of a platinum group metal with nickel or cobalt) during the agglomerate breaking step performed during the preparation of a dispersion comprising the electrocatalyst material, the ionically conductive material, and the diluent.

[0044] A suitable base metal binder may be capable of binding the base metal species up to an amount such that the weight % of the base metal species is at least 1 weight % based on the total weight of the bound base metal species and the base metal binder. The maximum amount of base metal species that the base metal binder may bind is not particularly limited. For example, not more than 20 weight %, typically not more than 10 weight %, based on the total weight of the bound base metal species and the base metal binder. Suitably, the base metal binder does not bind platinum group metals and therefore does not separate platinum group metals from the dispersion, for example, a suitable base metal binder binds less than 0.05 weight % of platinum group metals, preferably less than 0.02 weight % of platinum group metals, based on the total weight of the bound metal species and the base metal binder.

[0045] The base metal binder can be a base metal chelating agent. Therefore, the base metal binder comprises a chelating ligand that chelates the base metal substance. Preferably, the base metal chelating agent comprises a base metal chelating nitrogen-containing part, suitably a base metal chelating amino ligand. Therefore, the base metal chelating agent can comprise a multidentate, preferably a bidentate or tridentate amino ligand, the ligand comprising two or more, preferably two or three base metal chelating amino groups. The amino group can be a primary amine, a secondary amine or a tertiary amine, and includes a pyridyl group. Preferably, the base metal chelating agent comprises a mixture of a primary amine and a pyridyl group or a secondary amine and a pyridyl group. One or more amino groups in the amino group can be quaternized by an acid (such as sulfuric acid).

[0046] The base metal chelating nitrogen-containing moiety may be a multidentate amino ligand having the formula:

[0047]

[0048] wherein n+p=3; n=1 to 3; x=1 to 5, preferably 1 to 3, more preferably 1 or 2, for example 1; the pyridyl group is substituted at position 2, 3 or 4, preferably at position 2 or 3; the nitrogen atom can be quaternized by an acid such as sulfuric acid. Thus, the base metal chelating nitrogen-containing moiety includes aminomethylpyridine, for example 2-aminomethylpyridine, 3-aminomethylpyridine or bis-2 or bis-3-aminomethylpyridine, all of which can be quaternized by an acid such as sulfuric acid.

[0049] The base metal chelator may comprise a base metal chelating nitrogen-containing portion fixed on a solid support. In this regard, the base metal chelator comprises a base metal chelating nitrogen-containing portion and a solid support material, preferably consisting of a base metal chelating nitrogen-containing portion and a solid support material (or only comprising a base metal chelating nitrogen-containing portion and a solid support material). Therefore, the base metal chelator may be a chelating ion exchange resin. Suitably, the base metal chelator is covalently attached to a solid support. The nature of the support is not particularly limited. It may preferably be a polymer support. Preferably, the support is porous. Suitable polymer supports include polyalkylene polymers, such as polyvinyl polymers. A particularly suitable polyvinyl polymer is polystyrene. The term polystyrene in this sense is intended to include polymers and copolymers formed by styrene moieties, including polystyrene itself as well as poly (alpha-methylstyrene), poly (chlorostyrene) and poly (chloromethylstyrene). Poly (vinyl toluene) may also be suitable. The polymer of the polymer solid support may be cross-linked, for example, using a cross-linking agent (such as a divinyl aliphatic or aromatic compound, such as divinylbenzene). Suitably, the polymer may be a styrene-based divinylbenzene copolymer. Silica solid carrier (including porous silica solid carrier) may also be suitable. The solid carrier is usually a particulate solid carrier, but this is not necessary. The particle size is not particularly limited. Typical particle diameters are in the range of 450 μm to 600 μm and include these end values. For example, the particle may have a d50 particle diameter of at least 50 μm, at least 100 μm, at least 200 μm or at least 300 μm. For example, the particle may have a d50 particle diameter of no more than 5 mm, no more than 2 mm, no more than 1 mm, no more than 900 μm or no more than 800 μm.

[0050] In a specific example, the base metal chelator is a chelating ion exchange resin comprising a polydentate base metal chelating amino ligand preferably quaternized with an acid (preferably sulfuric acid) immobilized on a polystyrene (preferably styrene-divinylbenzene copolymer) support. An exemplary polydentate amine ligand is an aminomethyl pyridine, such as 2-aminomethyl pyridine, 3-aminomethyl pyridine, or bis-2 or bis-3-aminomethyl pyridine. Specific ion exchange resins include Dow Chemical Company's Series, such as M4195.

[0051] Alternatively, the base metal binder may be an acidic cation exchange resin, for example an acidic cation exchange resin comprising sulfonic acid functional groups, such as a sulfonated polystyrene cation exchange resin. The term polystyrene in this sense is intended to include polymers and copolymers formed from styrene moieties, such as styryl divinyl benzene known to those skilled in the art. Preferred cation exchange resins of this type are sulfonated styryl divinyl benzene copolymers, such as, for example Cation exchange resins such as IR120H.

[0052] The amount of base metal binder used can be expressed as a weight ratio of base metal binder to electrocatalyst material. The amount used is not particularly limited, but advantageously a relatively small amount relative to the electrocatalyst material can be used. Suitably, the weight ratio of base metal binder to electrocatalyst material is in the range of 1:20 to 1:1, preferably 1:20 to 1:3, more preferably 1:20 to 1:5 and including these end values.

[0053] The base metal binder can be contacted with the dispersion by dispersing the base metal binder in the dispersion. In order to remove the base metal binder, the dispersion can be filtered. Preferably, but not necessarily, the dispersion containing the base metal binder is stirred. There is no particular limitation on the manner in which the dispersion is stirred, and the technician will understand suitable stirring methods, such as stirring or drum rolling. The preferred method is drum rolling. The dispersion is suitably stirred for no more than 72 hours, for example no more than 48 hours, preferably no more than 24 hours. The dispersion is suitably stirred for at least 1 hour. Typically, the base metal binder is removed when the electrocatalyst ink is needed to form an electrocatalyst layer (for example, the electrocatalyst ink is ready and can be used immediately). However, this is not necessary, and the base metal binder can be removed at any time before the electrocatalyst layer is formed within the life of the electrocatalyst ink. No heating is required, which will damage the ink.

[0054] Alternatively, the base metal binder may be contacted with the dispersion by passing the dispersion through a column filled with the base metal binder. Preferably, no additional diluent is added when the dispersion passes through such a column. The size of the column, the pressure used, and the contact time between the dispersion and the base metal binder are not particularly limited, and the skilled person will be able to determine appropriate conditions based on, for example, the mass, composition, and solids content of the dispersion.

[0055] Alternatively, the base metal binder can be contacted with the dispersion by placing a container containing the base metal binder in the dispersion, wherein the container is permeable to the dispersion but impermeable to the base metal binder. Therefore, the base metal binder will not be dispersed in the dispersion. Instead, the dispersion will enter through the permeable wall of the container and contact the base metal binder while it remains in the container. Advantageously, no filtering step is required, and the container containing the base metal binder can be removed from the dispersion only at the required time. The characteristics of the container are not particularly limited, and can be, for example, a sealed mesh bag having holes of the correct size to make the dispersion permeable, but the base metal binder impermeable. For example, a heat-sealable polyethylene or polypropylene net can be used to prepare the container. When the container is in the dispersion, the dispersion can be agitated, and the technician will understand suitable agitation methods, such as stirring or drum rolling.

[0056] Advantageously, contact between the dispersion and the base metal binder can be carried out at ambient temperature (e.g., in the range of 20°C to 25°C and including these values), so no heating is required, which would damage the ink. The pH of the dispersion during contact depends on the nature of the ionomer present, and will preferably be about 2. Advantageously, the benefits of the present invention can be achieved without having to change the natural pH of the dispersion.

[0057] The electrocatalyst ink may contain additional components, which are preferably added after contact with the base metal binder. Such components include, but are not limited to: oxygen evolution catalysts; hydrogen peroxide decomposition catalysts; hydrophobic agents (e.g., polymers (such as polytetrafluoroethylene (PTFE) or inorganic solids) with or without surface treatment) or hydrophilic agents (e.g., polymers or inorganic solids, such as oxides) for controlling the transport characteristics of reactants and water. The selection of additional components is within the ability of the skilled artisan. Any additional solid components are included in the electrocatalyst ink solids content listed herein.

[0058] The third aspect of the present invention can also be considered as a method for preparing an electrocatalyst layer. In the third aspect of the present invention, the electrocatalyst ink can be applied to the substrate by any suitable technique known to those skilled in the art. Such techniques include, but are not limited to, gravure coating, slot die (slot, extrusion) coating, screen printing, rotary screen printing, inkjet printing, spraying, painting, rod coating, pad coating, gap coating techniques such as knife or scraper coating on a roller and metering rod application. The applied electrocatalyst ink is formed into an electrocatalyst layer by drying. The drying method is not particularly limited, and the technician will be able to determine a suitable method. For example, the electrocatalyst ink can be heated to a temperature in the range of 50°C to 250°C and including these end values.

[0059] The electrocatalyst layer of the present invention can be a cathode or an anode, preferably a cathode or an anode of a proton exchange membrane fuel cell. The characteristics of the electrocatalyst layer such as thickness, electrocatalyst loading, porosity, pore size distribution, average pore size and hydrophobicity will depend on whether it is used for an anode or a cathode. Specifically, the electrocatalyst layer is used for a cathode. In the anode, the electrocatalyst layer thickness is suitably at least 1 μm, typically at least 5 μm. In the anode, the electrocatalyst layer thickness is suitably no more than 15 μm, typically no more than 10 μm. In the cathode, the electrocatalyst layer thickness is suitably at least 2 μm, typically at least 5 μm. In the cathode, the electrocatalyst layer thickness is suitably no more than 20 μm, typically no more than 15 μm.

[0060] The electrocatalyst loading in the electrocatalyst layer will also depend on the intended use. In this context, electrocatalyst loading means the amount of active metal (e.g., platinum group metal) in the electrocatalyst layer. Thus, when the electrocatalyst is an alloy of platinum, the electrocatalyst loading is the amount of platinum per unit area, expressed as mg / cm 2 In a fuel cell cathode using a platinum electrocatalyst, the electrocatalyst loading is suitably at least 0.05 mg Pt / cm 2 , for example, no more than 0.7 mgPt / cm 2 , preferably not more than 0.3 mgPt / cm 2 In a fuel cell anode, the platinum loading in the electrocatalyst layer is suitably at least 0.02 mg Pt / cm 2 , for example, not more than 0.2 mg / Ptcm 2 , preferably not more than 0.15 mgPt / cm 2 .

[0061] In a fifth aspect of the invention, an electrocatalyst ink may be deposited onto a gas diffusion layer to form a gas diffusion electrode of the invention, i.e., a gas diffusion layer in combination with an electrocatalyst layer of the invention. The gas diffusion layer comprises a gas diffusion substrate and preferably a microporous layer. When a microporous layer is present, the electrocatalyst ink is deposited onto the microporous layer. Typical gas diffusion substrates include nonwoven paper or webs comprising a carbon fiber web and a thermosetting resin binder (e.g., TGP-H series carbon fiber paper available from Toray Industries Inc., Japan, or H2315 series available from Freudenberg FCCT KG, Germany, or TEFLON® available from SGL Technologies GmbH, Germany). series, or from Ballard Power Systems Inc. series), or woven carbon cloth. Prior to manufacturing the electrodes and incorporating into the membrane electrode assembly, the carbon paper, mesh or cloth may be provided with a pretreatment to make it more wettable (hydrophilic) or more water-repellent (hydrophobic). The nature of any treatment will depend on the type of fuel cell and the operating conditions to be used. The substrate may be made more wettable by incorporating a material such as amorphous carbon black via impregnation from a liquid suspension, or the substrate may be made more hydrophobic by impregnating the pore structure of the substrate with a colloidal suspension of a polymer such as PTFE or polyfluoroethylene propylene (FEP), followed by drying and heating to above the melting point of the polymer. A typical microporous layer comprises a mixture of carbon black and a polymer such as polytetrafluoroethylene (PTFE).

[0062] In a seventh aspect of the invention, an electrocatalyst ink may be applied to a transfer substrate to form a catalytic transfer substrate of the invention. The catalytic transfer substrate of the invention comprises a transfer substrate and an electrocatalyst layer of the invention. Additional layers may be deposited on the exposed surface of the electrocatalyst layer before removing the transfer substrate; for example, an ion-conducting ionomer layer may be applied from a dispersion of ionomers using any suitable deposition technique known as described above for the deposition of the electrocatalyst layer. Additional additional layers may be added as needed, for example as described in PCT patent application number GB2015 / 050864. The transfer substrate is removed from the electrocatalyst layer at an appropriate time. The transfer substrate may be formed of any suitable material from which the electrocatalyst layer may be removed without damage. Examples of suitable materials include fluoropolymers such as polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene (ETFE), perfluoroalkoxy polymers (PFA), fluorinated ethylene propylene (FEP-copolymer of hexafluoropropylene and tetrafluoroethylene)) and polyolefins such as biaxially oriented polypropylene (BOPP).

[0063] In the ninth aspect of the present invention, the electrocatalyst ink of the present invention may be applied directly to one or both faces of an ion-conducting membrane to form a catalyst-coated ion-conducting membrane of the present invention. For example, one ink will contain a cathode electrocatalyst, while the other ink will contain an anode electrocatalyst. If the electrocatalyst ink of the present invention is applied to only one face of an ion-conducting membrane, the electrocatalyst layer may be applied to the other face by other conventional means. Alternatively, in the tenth aspect of the present invention, the catalyst-coated membrane of the present invention may be prepared by transferring the electrocatalyst layer of the present invention from the catalytic transfer substrate of the present invention to one or both faces of an ion-conducting membrane. If the electrocatalyst layer of the present invention is transferred to one face of an ion-conducting membrane, the electrocatalyst layer may be applied to the other face by other conventional means. The ion-conducting membrane of the present invention may also be prepared by a mixture of the ninth aspect and the tenth aspect of the present invention, i.e., one electrocatalyst layer may be applied according to the method of the ninth aspect of the present invention, and another electrocatalyst layer may be applied according to the method of the tenth aspect of the present invention.

[0064] The faces of the ion-conducting membrane referred to herein are separated by the thickness of the ion-conducting membrane. The skilled person will understand that the thickness refers to the measurement in the through-plane, z-direction. The opposite face extends perpendicular to the thickness (i.e. in the xy plane). Preferably, the ion-conducting membrane is any membrane suitable for use in a proton exchange membrane fuel cell, for example, the membrane may be based on a perfluorinated sulfonic acid material such as (Chemours Company), (Solvay Specialty Polymers)、 (Asahi Glass Group) and (Asahi Kasei Chemicals Corp.). Alternatively, the membrane may be based on a sulfonated hydrocarbon membrane, such as that available from FuMA-Tech GmbH (as P, E or K series products), those of JSR Corporation, Toyobo Corporation, etc.

[0065] The thickness of the ion-conducting membrane is not particularly limited and will depend on the intended application of the ion-conducting membrane. For example, a typical fuel cell ion-conducting membrane has a thickness of at least 5 μm, suitably at least 8 μm, preferably at least 10 μm. A typical fuel cell ion-conducting membrane has a thickness of no more than 50 μm, suitably no more than 30 μm, preferably no more than 20 μm. Therefore, a typical fuel cell ion-conducting membrane has a thickness in the range of 5 μm to 50 μm, suitably 8 μm to 30 μm, preferably 10 μm to 20 μm and including these end values.

[0066] The ion-conducting membrane may include additional components, such as peroxide decomposition catalysts and / or free radical decomposition catalysts and / or recombination catalysts. The recombination catalyst catalyzes the recombination of unreacted H2 and O2, which can diffuse from the anode and cathode of the fuel cell into the ion-conducting membrane, respectively, to produce water. The ion-conducting membrane may also include reinforcing materials embedded in the thickness of the ion-conducting membrane, such as planar porous materials (ePTFE (ePTFE) described in, for example, USRE37307), to provide improved mechanical strength of the ion-conducting membrane, such as enhanced tear resistance and reduced hydration and dehydration dimensional changes, and thus further increase the durability of the membrane electrode assembly and the life of the fuel cell incorporating the catalytic ion-conducting membrane of the present invention. Other methods for forming an enhanced ion-conducting membrane include those disclosed in US 7,807,063 and US 7,867,669, in which the reinforcing member is a rigid polymer membrane, such as polyimide, in which a plurality of holes are formed, and then filled with PFSA ionomers.

[0067] Any reinforcement present may extend over the entire thickness of the ion-conducting membrane, or over only a portion of the thickness of the ion-conducting membrane. It may also be advantageous to reinforce the periphery of the first and second surfaces of the ion-conducting membrane to a greater extent than the center planes of the first and second surfaces of the ion-conducting membrane. Conversely, it may be desirable to reinforce the center of the first or second surface of the ion-conducting membrane to a greater extent than the periphery of the first or second surface of the ion-conducting membrane.

[0068] The method for preparing the membrane electrode assembly of the twelfth aspect of the present invention may suitably be carried out as follows:

[0069] (i) applying a gas diffusion electrode of the invention to each side of the ion-conducting membrane. Preferably, the layers are then laminated together;

[0070] (ii) applying a gas diffusion electrode of the invention to one face of a catalyst-coated ion-conducting membrane, wherein only one side comprises an electrocatalyst layer, and applying the gas diffusion layer to the electrocatalyst layer. The catalyst-coated ion-conducting membrane may be a catalyst-coated ion-conducting membrane of the invention comprising an electrocatalyst layer of the invention.

[0071] The method for preparing the membrane electrode assembly of the fourteenth aspect of the present invention may suitably be carried out as follows:

[0072] (i) applying a gas diffusion layer to the two electrocatalyst layers of the ion-conducting membrane of the invention;

[0073] (ii) applying a gas diffusion electrode to one face of an ion-conducting membrane of the invention, wherein only one side comprises an electrocatalyst layer, and applying the gas diffusion layer to the electrocatalyst layer. The gas diffusion electrode may be a gas diffusion electrode of the invention.

[0074] Although the present invention is discussed primarily with reference to its use in preparing an electrocatalyst ink for a fuel cell electrocatalyst layer, the skilled person will appreciate that the method is applicable to preparing an electrocatalyst ink for an electrocatalyst layer for an electrolyzer. Thus, the electrocatalyst layer of the present invention may be an electrocatalyst layer for an electrolyzer, preferably an electrocatalyst layer for a proton exchange membrane electrolyzer. Moreover, in a seventeenth aspect, the present invention provides an electrolyzer comprising a membrane electrode assembly of the present invention. Preferably, the electrolyzer is a proton exchange membrane electrolyzer.

[0075] Example

[0076] Electrocatalyst ink preparation

[0077] Five electrocatalyst inks E1, E2, E3, E4 and C1 were prepared.

[0078] • E1 contained a dealloyed 30 wt% Pt2Ni / C electrocatalyst and 800EW PFSA ionomer, supplied by 3M under the name 3M 800EW.

[0079] • E2 contained a dealloyed 30 wt% Pt2Ni / C electrocatalyst and 700 EW PFSA ionomer, supplied by Asahi Glass under the name IQ171.

[0080] • E3 contained a dealloyed 30 wt% Pt2Ni / C electrocatalyst and 950EW PFSA ionomer supplied by The Chemours Company under the name DE2020CS.

[0081] E4 contained 10 wt% PtPtNi2 / C electrocatalyst and 800EW PFSA ionomer, supplied by 3M under the name 3M800EW. The electrocatalyst was not subjected to a dealloying step.

[0082] C1 contained a dealloyed 30 wt% Pt2Ni / C electrocatalyst and 800EW PFSA ionomer, supplied by 3M under the name 3M 800EW.

[0083] As will be appreciated by the skilled artisan, demetallization removes a portion of the nickel from the surface of the PtNi catalyst. The dealloyed catalyst is prepared by a standard approach involving first using a method similar to the general method for preparing a carbon-supported platinum catalyst described in WO2013 / 015894 and using a carbon specifically designed for fuel cell applications disclosed in WO2013 / 015894 to prepare a particulate carbon-supported nanoparticle (Pt / C) material. A solution of nickel nitrate in water is added to aliquots in a dry Pt / C catalyst dispersed in H2O and mixed to ensure a uniform dispersion. Once deposition is complete, the PtNi / C material is recovered, dried and annealed at 900°C for one hour in a reducing atmosphere of 5% H2 / N2 to alloy the platinum and nickel. The alloyed PtNi / C material is then deposited in an aqueous and subsequently alcoholic H2SO4 solution (20 ml g -1 The electrocatalyst in E4 was not subjected to this final step of washing in aqueous and then alcoholic H2SO4 solutions, so it was not dealloyed.

[0084] Electrocatalyst inks were prepared by mixing 16 g (E1), 15 g (E2) and (E3) or 20 g (E4) electrocatalyst, 8.7 g (E1), 8.0 g (E2), 8.0 g (E3) and 9.4 g (E4) ionomer, and solvent to form a dispersion such that the total amount of electrocatalyst ink was 205.9 g (E1), 191.7 g (E2), 191.7 g (E3) and 244.8 g (E4). The inks were prepared to contain about 12 wt% solids (electrocatalyst and ionomer). The dispersants used were 80 wt% 1-propanol in water (E1, E3, E4 and C1) or 10 wt% ethanol and 70 wt% 1-propanol in water (E2). The mixtures were bead milled together to form a well-dispersed ink. Some material was lost during bead milling (due to the relatively small batch size produced, the loss percentage was relatively high), so that the total amount of electrocatalyst ink produced was 150 g (E1), 116.7 g (E2), 127.3 g (E3) and 140.3 g (E4). The actual solids content of the ink after milling was 11.9 wt% (E1), 12.1 wt% (E2), 11.7 wt% (E3) and 11.8 wt% (E4).

[0085] Example 1 - Base Metal Binder Capacity

[0086] The electrocatalyst inks E1, E2, and E3 were placed in a sealed container and 3.67 g (E1), 2.85 g (E2), or 3.11 g (E3) of a base metal binder from Dow Chemical Company were added. M4195 resin. In each ink, the weight ratio of base metal binder to electrocatalyst material (after grinding) was about 1:3. The sealed container was then drum rolled for 48 hours and then the base metal binder was removed by filtration. The nickel content of the resin (weight % of total resin and nickel) was analyzed by inductively coupled plasma mass spectrometry (ICPMS) and the results are provided in Table 1. It is clear that the base metal binder removes nickel species from the electrocatalyst ink.

[0087] Table 1

[0088] Ink wt%Ni Weight%Pt E1 0.81 <0.02 E2 1.9 <0.02 E3 1.88 <0.02

[0089] The electrocatalyst in ink E4 was not subjected to a dealloying step, meaning that a relatively large amount of free nickel species was present in the ink after milling that was not present in the dealloyed electrocatalyst inks (e.g., E1, E2, and E3). Therefore, this ink was used to determine the capacity of the base metal binder. Electrocatalyst ink E4 was placed in a sealed container and a first portion of 4.57 g of a base metal binder from Dow Chemical Company was added. M4195 resin. The weight ratio of base metal binder to electrocatalyst material (after grinding) is about 2:3. The sealed container is then drum rolled for 1 hour, and the base metal binder is then removed by filtration. A second portion of 4.21 g of the same base metal binder is then added, and the container is resealed and drum rolled for 24 hours, and then removed by filtration. A third portion of 3.87 g of the same base metal binder is then added, and the container is resealed and drum rolled for 24 hours, and then removed by filtration. Finally, a fourth portion of 3.17 g of the same base metal binder is added, and the container is resealed and drum rolled for 24 hours, and then removed by filtration.

[0090] The nickel content of each portion of base metal binder (wt % of total base metal binder and nickel) was analyzed by ICPMS. The results are provided in Table 2.

[0091] Table 2

[0092] part wt%Ni Weight%Pt Part 1 0.71 <0.02 Part 2 4.21 <0.02 Part 3 4.32 <0.02 Part 4 4.11 <0.02

[0093] It is apparent that after about one day of agitation with the ink, the base metal binder reaches a capacity of about 4 wt% nickel species, based on the total weight of nickel and base metal binder. Additionally, platinum is not absorbed by the base metal binder. Given this capacity, it is apparent that about one quarter to about one half of the base metal binder used with inks E1, E2, and E3 is actually required to remove free nickel species, since the base metal binder removes only about one quarter to one half of its full capacity.

[0094] Example 2 - Electrochemical Activity

[0095] Preparation of membrane electrode assembly

[0096] Two active areas of 50 cm were prepared by the following process 2 Catalyst-coated ion-conducting membranes: Anode and cathode catalyst layers were deposited onto PTFE sheets and the appropriate layers were transferred to either side of a PFSA reinforced membrane (15 μm thick) at a temperature between 150°C and 200°C.

[0097] In a catalyst coated ion conducting membrane, a base metal binder from Dow Chemical Company is used in a sealed container. After 48 hours of rolling with M4195, the electrocatalyst ink E1 showed a concentration of 0.2 mg Pt / cm 2 In another catalyst-coated ion-conducting membrane, the electrocatalyst ink C1 without contact with the base metal binder was used to prepare the cathode catalyst layer at a loading of 0.2 mg Pt / cm 2The cathode catalyst layer was prepared with a loading of 0.08 mg Pt / cm 2 Anode electrocatalyst ( 3000, nominal platinum loading on carbon support was 20 wt% platinum).

[0098] A gas diffusion layer was applied to each face of each catalyst-coated ion-conducting membrane to form a complete membrane electrode assembly. The gas diffusion layer used was a carbon fiber paper having a carbon fiber paper containing carbon and PTFE (from SGL Technologies GmbH) applied to the face in contact with the catalyst-coated ion-conducting membrane. 22BB) hydrophobic microporous layer.

[0099] Membrane electrode assembly performance test

[0100] Each 50 cm2 sample was measured in H2 / air at 80°C under fully humidified and pressurized (100% RH, 100 kPag) and drier ambient pressure (50% and 26% RH and ambient pressure) conditions using H2 and air flow rates of 1.5 and 2.0, respectively. 2 Polarization (current vs. voltage) performance of the membrane electrode assembly. Cell humidity (RH) and pressure were controlled at the anode and cathode inlets for testing at 100 kPag, and the outlet was at ambient pressure during ambient pressure testing.

[0101] As in Figure 1 , Figure 2 and Figure 3 As can be seen, electrocatalyst ink E1 prepared by the process of the present invention shows better performance at high current density compared to electrocatalyst ink C1 prepared by a process that does not include the step of contacting the electrocatalyst ink with a base metal binder.

[0102] A non-exhaustive list of aspects of the invention is provided in the following numbered clauses:

[0103] 1. A method for preparing an electrocatalyst ink, the method comprising the following steps:

[0104] i) preparing a dispersion comprising an electrocatalyst material, an ion-conducting material and a diluent; then

[0105] ii) contacting said dispersion with a base metal binder.

[0106] 2. The method of clause 1, wherein the electrocatalyst material comprises an electrocatalyst that is a platinum group metal or an alloy of a platinum group metal and a base metal.

[0107] 3. The method according to clause 1 or clause 2, wherein the electrocatalyst is supported on a support material.

[0108] 4. A method according to any preceding clause, wherein step i) comprises the step of breaking up agglomerates in the dispersion.

[0109] 5. The method according to clause 4, wherein the step of breaking up agglomerates in the dispersion is performed by ball milling.

[0110] 6. A method according to any preceding clause, wherein step ii) comprises dispersing the base metal binder in the dispersion prepared in step ii), and the method further comprises the step iii) of filtering the dispersion to remove the base metal binder.

[0111] 7. The method according to clause 6, wherein the dispersion is agitated in step ii).

[0112] 8. The method according to any one of clauses 1 to 5, wherein step ii) comprises passing the dispersion through a column packed with the base metal binder.

[0113] 9. A method according to any one of clauses 1 to 5, wherein step ii) comprises placing a container containing the base metal binder in the dispersion, wherein the container is permeable to the dispersion but impermeable to the base metal binder.

[0114] 10. A method according to any preceding clause, wherein the base metal binder is a base metal chelator.

[0115] 11. The method of clause 10, wherein the base metal chelating agent comprises a base metal chelating nitrogen-containing moiety.

[0116] 12. The method according to any one of clauses 1 to 9, wherein the base metal binder is an acidic cation exchange resin.

[0117] 13. A method of applying an electrocatalyst layer to a substrate, the method comprising the steps of:

[0118] i) preparing an electrocatalyst ink by a method according to any one of clauses 1 to 12; then

[0119] ii) applying the electrocatalyst ink to the substrate, and drying the ink to form an electrocatalyst layer.

[0120] 14. An electrocatalyst layer obtainable by a method according to clause 13.

[0121] 15. A method of making a gas diffusion electrode, the method comprising applying an electrocatalyst layer to a substrate according to the method of clause 13, wherein the substrate is the face of the gas diffusion layer.

[0122] 16. A gas diffusion electrode obtainable by a method according to clause 15.

[0123] 17. A method of preparing a catalytic transfer substrate, the method comprising applying an electrocatalyst layer to a substrate according to the method of clause 13, wherein the substrate is a face of a transfer substrate.

[0124] 18. A catalytic transfer substrate obtainable by the method according to clause 17.

[0125] 19. A method of preparing a catalyst coated ion conducting membrane, the method comprising applying an electrocatalyst layer to a substrate according to the method of clause 13, wherein the substrate is a face of the ion conducting membrane.

[0126] 20. A method of preparing a catalyst coated ion conducting membrane, the method comprising applying an electrocatalyst layer to the ion conducting membrane by transfer printing from a catalytic transfer substrate prepared according to the method of clause 17.

[0127] 21. A catalyst-coated ion-conducting membrane obtainable by a method according to clause 19 or clause 20.

[0128] 22. A method for preparing a membrane electrode assembly, the method comprising the following steps;

[0129] i) preparing a gas diffusion electrode according to the method of clause 15;

[0130] ii) applying the gas diffusion electrode prepared in step i) to the face of the ion-conducting membrane.

[0131] 23. A method for preparing a membrane electrode assembly, the method comprising the following steps;

[0132] i) preparing a catalyst-coated ion-conducting membrane according to the method of clause 19 or clause 20;

[0133] ii) applying a gas diffusion layer to the electrocatalyst layer.

[0134] 24. A membrane electrode assembly obtainable by the method according to clause 22 or clause 23.

[0135] 25. A fuel cell comprising the membrane electrode assembly according to clause 24.

Claims

1. A method for preparing an electrocatalyst ink, the method comprising the following steps: i) preparing a dispersion comprising an electrocatalyst material, an ion conductive material and a diluent; Then ii) contacting the dispersion with a base metal binder to remove free base metal species from the dispersion, wherein the base metal binder is a base metal chelating agent.

2. The method of claim 1, wherein the ion-conducting material is a proton-conducting ionomer.

3. The method according to claim 1 or 2, wherein the electrocatalyst material comprises an electrocatalyst which is a platinum group metal or an alloy of a platinum group metal and a base metal.

4. The method according to claim 1 or 2, wherein the electrocatalyst is supported on a support material.

5. The method according to claim 1 or 2, wherein step i) comprises the step of breaking up agglomerates in the dispersion.

6. The method according to claim 5, wherein the step of breaking up agglomerates in the dispersion is performed by ball milling.

7. The method according to claim 1 or 2, wherein step ii) comprises dispersing the base metal binder in the dispersion prepared in step ii), and the method further comprises the step iii) of filtering the dispersion to remove the base metal binder.

8. The process according to claim 7, wherein the dispersion is agitated in step ii).

9. The method of claim 1 or 2, wherein step ii) comprises passing the dispersion through a column packed with the base metal binder.

10. The method of claim 1 or 2, wherein step ii) comprises placing a container containing the base metal binder in the dispersion, wherein the container is permeable to the dispersion but impermeable to the base metal binder.

11. The method of claim 1 wherein the base metal chelating agent comprises a base metal chelating nitrogen-containing moiety.

12. The method of claim 1 or 2, wherein the base metal binder is an acidic cation exchange resin.

13. A method of applying an electrocatalyst layer to a substrate, the method comprising the steps of: i) preparing an electrocatalyst ink by the method according to claim 1; Then ii) applying the electrocatalyst ink to the substrate, and drying the ink to form an electrocatalyst layer.

14. An electrocatalyst layer obtainable by the method according to claim 13.

15. A method of making a gas diffusion electrode, the method comprising applying an electrocatalyst layer to a substrate according to the method of claim 13, wherein the substrate is the face of a gas diffusion layer.

16. A gas diffusion electrode obtainable by the method according to claim 15.

17. A method of preparing a catalytic decal transfer substrate, the method comprising applying an electrocatalyst layer to a substrate according to the method of claim 13, wherein the substrate is a face of a decal transfer substrate.

18. A catalytic decal transfer substrate obtainable by the method according to claim 17.

19. A method of making a catalyst coated ion conducting membrane, the method comprising applying an electrocatalyst layer to a substrate according to the method of claim 13, wherein the substrate is a face of the ion conducting membrane.

20. A method of making a catalyst coated ion conducting membrane comprising applying an electrocatalyst layer to the ion conducting membrane by decal transfer from a catalytic decal transfer substrate prepared according to the method of claim 17.

21. A catalyst-coated ion-conducting membrane obtainable by the method according to claim 19 or claim 20.

22. A method for preparing a membrane electrode assembly, the method comprising the following steps; i) preparing a gas diffusion electrode according to the method of claim 15; ii) applying the gas diffusion electrode prepared in step i) to the face of the ion-conducting membrane.

23. A method for preparing a membrane electrode assembly, the method comprising the following steps; i) preparing a catalyst-coated ion-conducting membrane according to the method of claim 19 or claim 20; ii) applying a gas diffusion layer to the electrocatalyst layer.

24. A membrane electrode assembly obtainable by the method according to claim 22 or claim 23.

25. A fuel cell comprising the membrane electrode assembly according to claim 24.

Citation Information

Patent Citations

  • Solid polymer electrolyte composite membrane comprising plasma etched porous support

    US7807063B2

  • Solid polymer electrolyte composite membrane comprising laser micromachined porous support

    US7867669B2

  • Catalyst layer

    WO2012080726A1

  • Nucleation of aluminum nitride on a silicon substrate using an ammonia preflow

    WO2013015894A2

  • Carbon supported catalyst

    WO2013045894A1